Pole piece, electrochemical device and electronic device

By setting up coating with different adhesive power on the edge area of ​​the polar set, the problem of decreased volume energy density of electrochemical devices in the existing technology in the existing technologies and the increase in the volume energy density of electrochemical devices. The improvement of safety performance, while maintaining the volume energy density.

CN119361595APending Publication Date: 2025-01-24NINGDE AMPEREX TECHNOLOGY LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411444293.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2020-08-31
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The prior art loses the volume energy density of the electrochemical device when increasing the bonding force between the electrode sheet and the current collector, making it difficult to improve both electrical and safety performance.

Method used

Set the first and second coatings with different adhesive power on the edge area of ​​the polar set, so that the bonding force of the first coating and the collector is greater than the bonding force of the second coating and the streaming body to prevent The collector is stripped during the cycle.

Benefits of technology

Through this method, the electrical performance and safety performance of electrochemical devices is improved, while minimizing the effects of volume energy density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361595A_ABST
    Figure CN119361595A_ABST
Patent Text Reader

Abstract

The invention provides a pole piece, an electrochemical device and an electronic device. The pole piece comprises a current collector which comprises a first edge region, a second edge region and a middle region located between the first edge region and the second edge region in the width direction; a first coating including a first portion and a second portion disposed on the first edge region and the second edge region, respectively; a part of the second coating is arranged on the middle area, the other part of the second coating is arranged on the first coating, and the second coating comprises an active material; wherein a first bonding force exists between the first part and the first edge area, a second bonding force exists between the second part and the second edge area, a third bonding force exists between the second coating and the middle area, and the first bonding force and the second bonding force are both larger than the third bonding force. The embodiments of the present application improve the electrical performance and safety performance of the electrochemical device while minimizing the influence on the volumetric energy density of the electrochemical device.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of the invention patent with application number 202080009959.5 (international application number: PCT / CN2020 / 112470) filed on August 31, 2020, whose invention name is "Electrode, electrochemical device and electronic device". Technical Field

[0002] The present application relates to the field of electronic technology, and in particular to pole pieces, electrochemical devices and electronic devices. Background Art

[0003] At present, in order to ensure the processing and safety performance of the pole piece, a bottom coating is usually added between the current collector and the active material layer. Although adding a bottom coating can significantly improve the adhesion between the pole piece and the current collector, it will lose the volume energy density of the electrochemical device (for example, lithium-ion battery). How to improve the electrical performance of the electrochemical device while ensuring its volume energy density is a problem to be solved. Summary of the invention

[0004] The present application adds a bottom coating to a specific area, thereby improving the electrical performance and safety performance of the electrochemical device while minimizing the impact on the volume energy density of the electrochemical device.

[0005] An embodiment of the present application provides a pole piece, comprising: a current collector, comprising a first edge region, a second edge region and an intermediate region located between the first edge region and the second edge region in a width direction; a first coating, comprising a first portion and a second portion respectively arranged on the first edge region and the second edge region; and a second coating, wherein a portion of the second coating is arranged on the intermediate region and another portion of the second coating is arranged on the first coating, and the second coating comprises an active material; wherein a first bonding force exists between the first portion and the first edge region, a second bonding force exists between the second portion and the second edge region, and a third bonding force exists between the second coating and the intermediate region, and both the first bonding force and the second bonding force are greater than the third bonding force.

[0006] In some embodiments, the first portion has a width d1, the second portion has a width d2, the second coating has a width D, 1%≤d1 / D≤20%, 1%≤d2 / D≤20%.

[0007] In some embodiments, the first bonding force and the second bonding force are both 2 to 5 times the third bonding force; and / or the first bonding force and the second bonding force are both greater than 10 N / m.

[0008] In some embodiments, the thickness of the first coating layer is h, the thickness of the second coating layer is H, 0.5 μm<h<8 μm, 20 μm<H<200 μm.

[0009] In some embodiments, the first coating includes a first conductive agent and a first binder, the first conductive agent includes at least one of conductive carbon black, carbon nanotubes, conductive graphite, graphene, acetylene black or nano-carbon fibers; the first binder includes at least one of polyvinylidene fluoride, vinylidene fluoride-fluorinated olefin copolymer, polyvinyl pyrrolidone, polyacrylonitrile, polymethyl acrylate, polytetrafluoroethylene, sodium carboxymethyl cellulose, styrene-butadiene rubber, polyurethane, fluorinated rubber or polyvinyl alcohol; wherein the mass content of the first conductive agent is 30% to 80%; the mass content of the first binder is 20% to 70%.

[0010] In some embodiments, in the length direction of the current collector, the first portion and / or the second portion are non-continuously coated, and the ratio of the total coating length of the first portion to the coating length of the second coating layer is greater than 80%, and the ratio of the total coating length of the second portion to the length of the second coating layer is greater than 80%. In some embodiments, at least a portion of the current collector is etched.

[0011] In some embodiments, the first edge region and the second edge region are etched, and the roughness of the first edge region and the second edge region is 2 to 4 times that of the middle region.

[0012] Another embodiment of the present application provides an electrochemical device, comprising: a positive electrode sheet; a negative electrode sheet; and a separator, disposed between the positive electrode sheet and the negative electrode sheet; wherein the positive electrode sheet and / or the negative electrode sheet is any of the above-mentioned electrode sheets.

[0013] An embodiment of the present application further provides an electronic device, comprising the above-mentioned electrochemical device.

[0014] The present application arranges coatings with different adhesion forces on the edge region of the current collector so that the adhesion force between the coating and the current collector is greater than the adhesion force between the active material coating and the current collector, thereby preventing the current collector from peeling off during the cycle of the electrochemical device and improving the electrical performance and safety performance of the electrochemical device. At the same time, since the coating is only arranged on the edge region of the current collector, the impact on the volume energy density of the electrochemical device can be minimized. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 A front view of a pole piece according to an embodiment of the present application is shown.

[0016] Figure 2A top view of a first coating layer (continuous) and a current collector according to an embodiment of the present application is shown.

[0017] Figure 3 A top view of a first coating layer (discontinuous) and a current collector according to another embodiment of the present application is shown.

[0018] Figure 4 A front view of an electrode assembly of an electrochemical device according to an embodiment of the present application is shown. DETAILED DESCRIPTION

[0019] The following embodiments may enable those skilled in the art to more fully understand the present application, but do not limit the present application in any way.

[0020] like Figure 1 As shown, a front view (cross-sectional view) of a pole piece of an embodiment of the present application is provided. The pole piece may include a current collector 1, and the current collector 1 includes a first edge region 4, a second edge region 5, and an intermediate region 6 located between the first edge region 4 and the second edge region 5 in the width direction. It should be understood that although Figure 1 The first edge region 4, the second edge region 5 and the middle region 6 are separated by dotted lines, but in fact there may be no boundary at the dotted lines. In some embodiments, the pole piece further includes a first coating 2, and the first coating 2 may include a first portion 7 and a second portion 8 respectively disposed on the first edge region 4 and the second edge region 5. In some embodiments, the material, width and thickness of the first portion 7 and the second portion 8 may be the same or different.

[0021] In some embodiments, the pole piece further includes a second coating 3, part of the second coating 3 is disposed on the middle region 6, and another part of the second coating 3 is disposed on the first coating 2, and the second coating 3 includes an active material. In some embodiments, there is a first bonding force between the first portion 7 and the first edge region 4, a second bonding force between the second portion 8 and the second edge region 5, and a third bonding force between the second coating 3 and the middle region 6, and both the first bonding force and the second bonding force are greater than the third bonding force. In the embodiment of the present application, by disposing the first coating 2 on the first edge region 4 and the second edge region 5 of the current collector 1, the bonding force between the first coating 2 and the current collector 1 is greater than the bonding force between the second coating 3 and the middle region 6, thereby preventing the current collector 1 and the second coating 3 from peeling off during the cycle of the electrochemical device, improving the electrical performance and safety performance of the electrochemical device, and at the same time, since the coating is only disposed on the first and second edge regions 4, 5 of the current collector 1, the impact on the volume energy density of the electrochemical device can be minimized.

[0022] In some embodiments, the first portion 7 has a width d1, the second portion 8 has a width d2, and the second coating 3 has a width D, 1%≤d1 / D≤20%, 1%≤d2 / D≤20%. If the width of the first portion 7 or the second portion 8 is too small, for example, less than 1% of the width of the second coating 3, the first coating 2 has limited effect on improving the bonding force between the second coating 3 and the current collector 1. Generally, because the binder content in the second coating is limited, the bonding force between it and the current collector is also relatively limited. If the first coating is not provided between the current collector and the second coating, the expansion and contraction of the second coating during the cycle process easily causes the second coating to peel off from the current collector. By providing the first coating and increasing the binder content in the first coating, the bonding force between the second coating and the current collector is improved, thereby avoiding the peeling between the second coating and the current collector. If the width of the first portion or the second portion is too large, for example, greater than 20% of the width of the second coating, it will adversely affect the volume energy density of the electrochemical device. In some embodiments, to further reduce the impact on the volumetric energy density of the electrochemical device while still achieving a greater adhesion between the first coating and the current collector, 1%≤d1 / D≤10%, 1%≤d2 / D≤10%.

[0023] In some embodiments, the first bonding force and the second bonding force are both 2 to 5 times the third bonding force. In some embodiments, the first bonding force and the second bonding force are both greater than 10 N / m. In this way, the bonding force between the second coating and the current collector can be improved.

[0024] In some embodiments, the thickness of the first coating 2 is h, the thickness of the second coating 3 is H, 0.5 μm<h<8 μm, 20 μm<H<200 μm. The thickness H of the second coating refers to the thickness of the second coating 3 on the middle region 6, or the sum of the thicknesses of the first portion 7 of the first coating 2 and the second coating 3 on the first edge region 4, or the sum of the thicknesses of the second portion 8 of the first coating 2 and the second coating 3 on the second edge region 5. If the thickness of the first coating is too small, for example, less than 0.5 μm, the effect of improving the bonding force between the second coating and the current collector is limited. If the thickness of the first coating is too large, the volume energy density of the electrochemical device will be adversely affected. If the thickness of the second coating is too small, the amount of active material per unit area will be too small, affecting the volume energy density of the electrochemical device. If the thickness of the second coating is too large, the insertion and extraction efficiency of lithium ions will be affected due to the long movement path of the insertion and extraction of lithium ions at the second coating near the current collector.

[0025] In some embodiments, the first coating 2 includes a first conductive agent and a first binder. In some embodiments, the first conductive agent includes at least one of conductive carbon black, carbon nanotubes, conductive graphite, graphene, acetylene black or nano-carbon fibers. In some embodiments, the first binder includes at least one of polyvinylidene fluoride, copolymer of vinylidene fluoride-fluorinated olefins, polyvinyl pyrrolidone, polyacrylonitrile, polymethyl acrylate, polytetrafluoroethylene, sodium carboxymethyl cellulose, styrene-butadiene rubber, polyurethane, fluorinated rubber or polyvinyl alcohol. In some embodiments, the mass content of the first conductive agent in the first coating is 30% to 80%, and the mass content of the first binder is 20% to 70%. If the mass content of the first conductive agent is too small, the conductivity of the first coating will be adversely affected. If the mass content of the first conductive agent is too large, the mass content of the first binder will be too small, affecting the bonding performance of the first coating.

[0026] It should be understood that although Figure 1 , the first coating layer 2 and the second coating layer 3 are formed on both sides of the current collector 1 , but this is merely exemplary, and the first coating layer 2 and the second coating layer 3 may be formed only on one side of the current collector 1 .

[0027] like Figure 2 , a top view of a first coating layer (continuous) and a current collector according to an embodiment of the present application is shown. For simplicity, only the middle region 6 of the current collector 1 and the first portion 7 and the second portion 8 of the first coating layer 2 are shown. Figure 2 The dotted lines in the figure show the stripping positions of the pole pieces. By providing the first coating 2 on the edge region of the current collector, the influence of stress during stripping and the generation of burrs of the current collector during stripping can be reduced. In some embodiments, the first portion 7 and / or the second portion 8 can be continuously coated in the length direction of the current collector 1.

[0028] like Figure 3 As shown, in some embodiments, in the length direction of the current collector 1, the first portion 7 and / or the second portion 8 may be non-continuously coated, and the ratio of the total coating length of the first portion 7 to the length of the second coating 3 is greater than 80%, and the ratio of the total coating length of the second portion 8 to the length of the second coating 3 is greater than 80%. By adopting the non-continuous coating method, the impact on the volume energy density of the electrochemical device is further reduced. In addition, if the coating length of the first portion 7 and / or the second portion 8 is too small, it will affect the full play of the bonding performance of the first coating 2.

[0029] In some embodiments, at least part of the region or all of the region in the current collector 1 is etched. By etching the current collector 1, the roughness of the current collector can be increased accordingly, thereby increasing the bonding force between the current collector and the first coating or the second coating. In some embodiments, the first edge region and the second edge region are etched, and the roughness of the first edge region 4 and the second edge region 5 is 2 to 4 times that of the middle region 6. By etching the first edge region 4 and the second edge region 5, the bonding force between the current collector 1 and the first coating 2 is further enhanced. In some embodiments, etching can be performed in the region where the current collector of the first coating is set. In some embodiments, etching is mainly performed by browning or blackening. Of course, etching can also be performed by other suitable methods. In some embodiments, the roughness of the etched area of ​​the current collector is 2 to 4 times that of the unetched area. In some embodiments, the roughness of the unetched area is less than 2μm.

[0030] It should be understood that the electrode of the present application can be either a positive electrode or a negative electrode. Figure 4 As shown, an embodiment of the present application further provides an electrochemical device, which includes an isolation membrane 11, a positive electrode sheet 12 and a negative electrode sheet 13, wherein the isolation membrane 11 is arranged between the positive electrode sheet 12 and the negative electrode sheet 13, wherein the positive electrode sheet 12 and / or the negative electrode sheet 13 are the electrodes of the above structure.

[0031] In some embodiments, the positive electrode current collector of the positive electrode sheet 12 may be aluminum (Al) foil, and of course, other positive electrode current collectors commonly used in the art may also be used. In some embodiments, the thickness of the positive electrode current collector may be 1 μm to 200 μm.

[0032] In some embodiments, when the pole piece is a positive pole piece 12, the active material of the second coating 3 may include at least one of lithium cobaltate, lithium manganate, lithium iron phosphate, lithium nickel cobalt manganate, lithium nickel cobalt aluminum or lithium nickel manganate. In some embodiments, the second coating 3 also includes a binder and a conductive agent. In some embodiments, the binder in the second coating 3 may include at least one of polyvinylidene fluoride, a copolymer of vinylidene fluoride-hexafluoropropylene, a styrene-acrylate copolymer, a styrene-butadiene copolymer, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, sodium carboxymethyl cellulose, polyvinyl acetate, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene or polyhexafluoropropylene. In some embodiments, the conductive agent in the second coating 3 may include at least one of conductive carbon black, Ketjen black, lamellar graphite, graphene, carbon nanotubes or carbon fibers. In some embodiments, the mass ratio of the positive active material, the conductive agent and the binder in the second coating 3 may be 91 to 99: 0.5 to 3: 0.5 to 6. It should be understood that the above description is only an example, and the positive electrode active material layer may adopt any other suitable material, thickness and mass ratio.

[0033] In some embodiments, the negative electrode current collector of the negative electrode plate 13 may be at least one of copper foil, nickel foil or carbon-based current collector, and of course, other negative electrode current collectors commonly used in the art may also be used. In some embodiments, the thickness of the negative electrode current collector may be 1 μm to 200 μm.

[0034] In some embodiments, when the pole piece is a negative pole piece 13, the active material of the second coating 3 may include at least one of artificial graphite, natural graphite, hard carbon, mesophase carbon microspheres, silicon alloys, tin alloys or pure silicon. In some embodiments, the second coating 3 may also include a conductive agent and a binder. The conductive agent in the second coating 3 may include at least one of conductive carbon black, Ketjen black, lamellar graphite, graphene, carbon nanotubes or carbon fibers. In some embodiments, the binder in the second coating 3 may include at least one of carboxymethyl cellulose (CMC), polyacrylic acid, polyvinyl pyrrolidone, polyaniline, polyimide, polyamide-imide, polysiloxane, styrene-butadiene rubber, epoxy resin, polyester resin, polyurethane resin or polyfluorene. It should be understood that the materials disclosed above are only exemplary, and the second coating 3 as the negative active material layer may adopt any other suitable material. In some embodiments, the mass ratio of the negative active material, the conductive agent and the binder in the second coating 3 may be 91-99:0-3:1-6. It should be understood that the above is only an example, and any other suitable mass ratio may be adopted.

[0035] In some embodiments, the isolation film 11 includes at least one of polyethylene, polypropylene, polyvinylidene fluoride, polyethylene terephthalate, polyimide or aramid. For example, polyethylene includes at least one selected from high-density polyethylene, low-density polyethylene or ultra-high molecular weight polyethylene. In particular, polyethylene and polypropylene have a good effect on preventing short circuits and can improve the stability of the battery through the shutdown effect. In some embodiments, the thickness of the isolation film is in the range of about 5 μm to 20 μm.

[0036] In some embodiments, the surface of the isolation membrane may further include a porous layer, the porous layer is disposed on at least one surface of the isolation membrane, the porous layer includes inorganic particles and a binder, the inorganic particles are selected from at least one of aluminum oxide (Al2O3), silicon oxide (SiO2), magnesium oxide (MgO), titanium oxide (TiO2), hafnium dioxide (HfO2), tin oxide (SnO2), cerium dioxide (CeO2), nickel oxide (NiO), zinc oxide (ZnO), calcium oxide (CaO), zirconium oxide (ZrO2), yttrium oxide (Y2O3), silicon carbide (SiC), boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. In some embodiments, the pores of the isolation membrane have a diameter in the range of about 0.01 μm to 1 μm. The binder of the porous layer is selected from at least one of polyvinylidene fluoride, copolymer of vinylidene fluoride and hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, sodium carboxymethyl cellulose, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene or polyhexafluoropropylene. The porous layer on the surface of the separator can improve the heat resistance, oxidation resistance and electrolyte wetting performance of the separator, and enhance the adhesion between the separator and the pole piece.

[0037] In some embodiments of the present application, the electrode assembly of the electrochemical device is a wound electrode assembly or a stacked electrode assembly.

[0038] In some embodiments, the electrochemical device includes a lithium ion battery, but the present application is not limited thereto. In some embodiments, the electrochemical device may further include an electrolyte. The electrolyte may be one or more of a gel electrolyte, a solid electrolyte, and an electrolyte, the electrolyte including a lithium salt and a non-aqueous solvent. The lithium salt is selected from one or more of LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, LiSiF6, LiBOB or lithium difluoroborate. For example, the lithium salt is selected from LiPF6 because it can provide high ionic conductivity and improve cycle characteristics.

[0039] The non-aqueous solvent may be selected from carbonate compounds, carboxylate compounds, ether compounds, other organic solvents or combinations thereof.

[0040] The carbonate compound may be selected from a chain carbonate compound, a cyclic carbonate compound, a fluorinated carbonate compound or a combination thereof.

[0041] The linear carbonate compound may be selected from diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC) and combinations thereof. The cyclic carbonate compound may be selected from ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinyl ethylene carbonate (VEC) or combinations thereof. The fluorocarbonate compound may be selected from fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, trifluoromethylethylene carbonate or combinations thereof.

[0042] The carboxylate compound may be selected from methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decanoic acid lactone, valerolactone, mevalonolactone, caprolactone, methyl formate, or a combination thereof.

[0043] The ether compound may be selected from dibutyl ether, tetraglyme, diglyme, 1,2-dimethoxyethane, 1,2-diethoxyethane, ethoxymethoxyethane, 2-methyltetrahydrofuran, tetrahydrofuran, or a combination thereof.

[0044] Other organic solvents may be selected from dimethyl sulfoxide, 1,2-dioxolane, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, formamide, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate, trioctyl phosphate, and phosphate esters or combinations thereof.

[0045] In some embodiments of the present application, taking a lithium-ion battery as an example, a positive electrode sheet, a separator, and a negative electrode sheet are wound or stacked in sequence to form an electrode component, and then encapsulated in, for example, an aluminum-plastic film, injected with an electrolyte, formed, and encapsulated to form a lithium-ion battery. Then, the prepared lithium-ion battery is subjected to a performance test.

[0046] Those skilled in the art will appreciate that the above-described method for preparing an electrochemical device (eg, a lithium-ion battery) is only an example, and other methods commonly used in the art may be used without departing from the disclosure of the present application.

[0047] Embodiments of the present application also provide electronic devices including the above-mentioned electrochemical devices. The electronic devices of the embodiments of the present application are not particularly limited, and they can be any electronic devices known in the prior art. In some embodiments, the electronic device can include, but is not limited to, a laptop computer, a pen-input computer, a mobile computer, an e-book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc.

[0048] Some specific embodiments and comparative examples are listed below to better illustrate the present application, wherein a lithium-ion battery is used as an example.

[0049] Example 1

[0050] Preparation of positive electrode sheet: The positive electrode active material lithium cobalt oxide, conductive agent conductive carbon black, and binder polyvinylidene fluoride (PVDF) are dissolved in N-methylpyrrolidone (NMP) solution at a weight ratio of 97.6:1.1:1.3 to form positive electrode slurry. Aluminum foil is used as the positive electrode current collector, and the positive electrode slurry is coated on the positive electrode current collector with a coating thickness of 50μm. After drying, cold pressing, and slitting, the positive electrode sheet is obtained.

[0051] Preparation of negative electrode sheet: Dissolve the first binder polyvinylidene fluoride and the first conductive agent conductive carbon black in N-methylpyrrolidone (NMP) solution at a weight ratio of 60:40 to form a first coating slurry. Use a copper foil with a thickness of 10μm and a width of 80mm as the negative electrode current collector, and apply the first coating slurry to the edge of the negative electrode current collector. The coating width of the two edge positions is 5mm and the thickness is 2μm. Dry to obtain the first coating;

[0052] The negative electrode active material artificial graphite and the binder styrene-butadiene rubber are dissolved in deionized water at a weight ratio of 98:2 to form a second coating slurry. The second coating slurry is applied to the negative electrode current collector and the first coating, dried, and cold pressed to obtain a negative electrode active material layer with a thickness of 60 μm. After cutting, a negative electrode sheet is obtained.

[0053] Preparation of isolation membrane: The isolation membrane substrate is 8 μm thick polyethylene (PE), and a 2 μm alumina ceramic layer is coated on both sides of the isolation membrane substrate. Finally, 2.5 mg of binder polyvinylidene fluoride (PVDF) is coated on both sides of the ceramic layer and dried.

[0054] Preparation of electrolyte: In an environment with a water content of less than 10 ppm, lithium hexafluorophosphate and a non-aqueous organic solvent (ethylene carbonate (EC): dimethyl carbonate (DMC) = 40:60, weight ratio) are prepared in a weight ratio of 8:92 to form an electrolyte.

[0055] Preparation of lithium-ion battery: stack the positive electrode sheet, separator, and negative electrode sheet in order, so that the separator is between the positive electrode sheet and the negative electrode sheet to play an isolating role, and wind them to obtain the electrode assembly. Place the electrode assembly in the outer packaging aluminum plastic film, remove moisture at 80°C, inject the above electrolyte and package, and obtain the lithium-ion battery through the process of formation, degassing, trimming, etc.

[0056] Other embodiments and comparative examples are parameter changes based on the steps of embodiment 1, wherein the two edge regions of the negative electrode current collector used for coating the first part and the second part in embodiment 5 are etched, the roughness of the etched edge region is 3 μm, and the roughness of other non-etched regions is 1 μm. The specific changed parameters are shown in the following table.

[0057] The test methods for various parameters of this application are described below.

[0058] Test method for volume energy density:

[0059] Place the lithium-ion battery in a 25℃ constant temperature box and let it stand for 30 minutes to allow the lithium-ion battery to reach a constant temperature. Charge the lithium-ion battery that has reached a constant temperature at a constant current of 0.5C to a voltage of 4.4V, then charge it at a constant voltage of 4.4V to a current of 0.05C, and discharge it at 0.5C to a voltage of 3.0V, and record the discharge energy.

[0060] Volume energy density = discharge energy / (length*width*thickness of lithium-ion battery).

[0061] Heavy object impact test of lithium-ion batteries:

[0062] At 25°C, the lithium-ion battery was charged at a constant current of 0.5C to a voltage of 4.4V, and then charged at a constant voltage of 4.4V to a current of 0.05C. The UL1642 test standard was adopted, wherein the weight was 9.8kg in mass, 15.8mm in diameter, and 61±2.5cm in drop height. The drop direction was parallel to the longitudinal direction of the isolation membrane. The lithium-ion battery was impact tested. The impact test was passed if the lithium-ion battery did not explode, catch fire, or emit smoke. Ten lithium-ion batteries were tested in each group, and the pass rate of the heavy object impact test of the lithium-ion battery was calculated (if 4 batteries passed the heavy object impact test, it was expressed as 4 / 10).

[0063] Table 1 shows various parameters and evaluation results of Examples and Comparative Examples.

[0064] Table 1

[0065]

[0066] By comparing Example 1 with Comparative Example 1, it can be seen that by applying the first coating only at the two edge areas of the current collector, the bonding force between the first coating and the current collector is greater than the bonding force between the second coating and the middle area of ​​the current collector. Because the bonding force between the second coating and the current collector is weak, it is easy to achieve the peeling of the active material coating and the current collector when impacting, which improves the impact test pass rate of the lithium ion battery from 4 / 10 to 8 / 10. In addition, due to the reduction in the coating area of ​​the first coating, the thickness of the electrode assembly of the lithium ion battery is smaller, and the volume energy density of the lithium ion battery is increased by 1%. It can be seen from Examples 2 to 5 that by adjusting the width of the first coating, the pass rate of the energy density and the impact test can be achieved, but the increase in the coating width will have a trend of decreasing the rate of improvement of the energy density. By comparing Example 5 with Example 1, it can be seen that by etching the edge area of ​​the current collector for coating the first coating, the bonding force between the first coating and the current collector can be improved, thereby increasing the impact test pass rate of the lithium ion battery to 9 / 10.

[0067] By comparing Examples 1 and 6 to 8, it can be seen that the adhesion between the first coating and the current collector is improved by increasing the thickness of the first coating. Generally, for a specific second coating thickness, there is an optimal value for the thickness of the first coating. A relatively small first coating thickness cannot guarantee a good coating state, and the adhesion with the current collector is limited. However, excessive thickness will cause overpressure in the active material of the second coating in the edge area, which will have a certain impact on the capacity. The thickness adjustment of the first coating has little effect on the impact test, and the pass rate can reach 8 / 10, while the volume energy density improvement rate tends to decrease with the increase of the thickness of the first coating.

[0068] By comparing Examples 1 and 9 to 11, it can be seen that for different second layer coating thicknesses, this method can be used to improve energy density and impact test pass rate, but after the thickness of the pole piece increases, the first layer coating has limited improvement on the overall energy density, which will decrease to a certain extent from 1% to 0.5%. The impact on the impact test pass rate is small.

[0069] By comparing Examples 1 and 12 to 14, it can be seen that by adjusting the binder content of the first coating, the bonding force between the edge of the first coating and the current collector can be achieved. Under certain circumstances, the energy density improvement is at the same level, and a 1% improvement effect can be achieved. When the bonding force content is low, such as less than 20%, the bonding force between the first coating and the current collector will be too weak, which will have an adverse effect on the thickness of the pole piece, and will lose part of the volume energy density, and the energy density improvement rate will be reduced to less than 0.8%. Because the bonding force between the second coating and the current collector is not changed, the impact on the pass rate of the impact test is small, and an 8 / 10 pass rate can be guaranteed.

[0070] By comparing Example 15 with Comparative Example 1, it can be seen that by making the bonding force between the first coating and the current collector greater than the bonding force between the second coating and the middle area of ​​the current collector, the impact test pass rate of the lithium ion battery is improved from 4 / 10 to 8 / 10. In addition, by adopting the method of discontinuous coating of the first coating and reducing the ratio of the width of the first coating to the second coating, the volume energy density of the lithium ion battery is increased by 1.3%.

[0071] The above description is only a preferred embodiment of the present application and an explanation of the technical principles used. Those skilled in the art should understand that the scope of disclosure involved in the present application is not limited to the technical solution formed by a specific combination of the above technical features, but should also cover other technical solutions formed by any combination of the above technical features or their equivalent features. For example, the above features are replaced with the technical features with similar functions disclosed in the present application.

Claims

1. A pole piece, characterized in that: include: a current collector, comprising a first edge region, a second edge region, and an intermediate region between the first edge region and the second edge region in a width direction; a first coating layer comprising a first portion and a second portion disposed on the first edge region and the second edge region, respectively, wherein the first coating layer is not disposed on the intermediate region; and a second coating layer, a portion of the second coating layer is disposed on the intermediate region, another portion of the second coating layer is disposed on the first coating layer, the second coating layer comprising an active material; There is a first bonding force between the first part and the first edge area, a second bonding force between the second part and the second edge area, a third bonding force between the second coating and the middle area, and both the first bonding force and the second bonding force are greater than the third bonding force.

2. The pole piece according to claim 1, wherein: The first portion has a width d1, the second portion has a width d2, the second coating has a width D, 1%≤d1 / D≤20%, 1%≤d2 / D≤20%.

3. The pole piece according to claim 1, wherein: The first bonding force and the second bonding force are both 2 to 5 times of the third bonding force; and / or the first bonding force and the second bonding force are both greater than 10 N / m.

4. The pole piece according to claim 1, wherein: The thickness of the first coating layer is h, the thickness of the second coating layer is H, 0.5 μm<h<8 μm, 20 μm<H<200 μm.

5. The pole piece according to claim 1, wherein: The first coating layer includes a first conductive agent and a first binder, wherein the first conductive agent includes at least one of conductive carbon black, carbon nanotubes, conductive graphite, graphene, acetylene black or nano-carbon fiber; The first binder comprises at least one of polyvinylidene fluoride, copolymer of vinylidene fluoride and fluorinated olefin, polyvinyl pyrrolidone, polyacrylonitrile, polymethyl acrylate, polytetrafluoroethylene, sodium carboxymethyl cellulose, styrene-butadiene rubber, polyurethane, fluorinated rubber or polyvinyl alcohol; Wherein, the mass content of the first conductive agent is 30% to 80%; the mass content of the first adhesive is 20% to 70%.

6. The pole piece according to claim 1, wherein: In the length direction of the current collector, the first part and / or the second part are non-continuously coated, and the ratio of the total coating length of the first part to the coating length of the second coating is greater than 80%, and the ratio of the total coating length of the second part to the coating length of the second coating is greater than 80%.

7. The pole piece according to claim 1, wherein: At least a portion of the current collector is etched.

8. The pole piece according to claim 7, wherein: The first edge region and the second edge region are etched, and the roughness of the first edge region and the second edge region is 2 to 4 times that of the middle region.

9. An electrochemical device, characterized in that: include: Positive electrode; Negative electrode; as well as A separator, disposed between the positive electrode sheet and the negative electrode sheet; Wherein, the positive electrode sheet and / or the negative electrode sheet is a sheet according to any one of claims 1 to 8.

10. An electronic device, characterized in that: Comprising the electrochemical device according to claim 9.

Citation Information

Patent Citations

  • Pole piece, electrochemical device and electronic device

    CN113330601A

  • Electrode pole piece and lithium ion battery

    CN207233865U

  • Mass flow body, electrode pole piece and lithium ion battery

    CN207353383U